Relationship between Comorbid Diseases History and Quality Of Life Post Covid-19 Infection on Health Service Officers - Agustini Prasetiya Ningrum, Kartika (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
Covid-19 infection affects the body's organ system which ultimately has a negative impact on health-related quality of life. The purpose of this study was to determine the relationship between a comorbid diseases history and quality of life. This type of research is quantitative with a cross-sectional approach, with a sample of 41 employees of Demang Sepulau Raya Hospital, Central Lampung after being infected with Covid-19 using simple random sampling. The data collection tool was a questionnaire. Data analysis used percentages and the Chi-Square test. The results of the study found that most respondents had no comorbidities (87.8%), good physical function (95.1%), poor physical limitations (78.0%) and good physical pain (82.9%). Most respondents who had comorbid diseases had good physical function (100%), poor physical limitations (80.0%), and bad physical pain (60.0%). At the same time, most respondents who did not have comorbid diseases were those who had poor physical function (5.60%), good physical limitations (22.2%), and good physical pain (88.9%). There was no relationship between the history of comorbid diseases and physical function (p=1,000) and physical limitations (p=1,000), there was a relationship between the history of comorbid diseases and physical pain (p=0.028). ABSTRAK Infeksi Covid-19 berpengaruh pada sistem organ tubuh yang akhirnya berdampak buruk pada kualitas hidup terkait kesehatan. Tujuan penelitian ini adalah mengetahui hubungan antara riwayat penyakit komorbid dengan kualitas hidup. Jenis penelitian ini kuantitatif dengan pendekatan cross sectional, dengan jumlah sampel 41 orang karyawan RSUD Demang Sepulau Raya Lampung Tengah pasca terinfeksi Covid-19 menggunakan simple random sampling. Alat pengumpul data kuesioner. Analisis data menggunakan persentase dan uji Chi-Square. Hasil penelitian mendapatkan bahwa sebagian besar responden tidak ada komorbid sebanyak 87,8%, fungsi fisik baik sebanyak 95,1%, keterbatasan fisik buruk sebanyak 78,0% dan nyeri fisik baik sebanyak 82,9%. Responden yang memiliki penyakit penyerta sebagian besar memiliki fungsi fisik baik (100%), keterbatasan fisik buruk (80,0%), dan nyeri fisik hebat (60,0%). Sementara itu, responden yang tidak memiliki penyakit penyerta sebagian besar memiliki fungsi fisik buruk (5,60%), keterbatasan fisik baik (22,2%), dan nyeri fisik hebat (88,9%). Tidak ada hubungan riwayat penyakit komorbid dengan fungsi fisik (p=1,000) dan keterbatasan fisik (p=1,000), ada hubungan riwayat penyakit komorbid dengan nyeri fisik (p=0,028).